Pengaruh Literasi Keuangan Terhadap Perilaku Kredit Berisiko Yang Dimediasi Oleh Efikasi Diri Pada Mahasiswa di Kota Surakarta: Literasi Keuangan Mahasiswa - Mukharomah; Kurniawan, Muhammad Randhy; Noorbaiti (Benefit: Jurnal Manajemen dan Bisnis, 2023)
The effect of financial literacy on students in Surakarta amid the development of fintech on risky credit behavior mediated by financial self-efficacy is interesting to study. Because financial literacy always develops from time to time. The research sample totaled 150 respondents from students who used risky credit. The primary data in this study is the data used. Questionnaires were used to collect data in this study. The analysis uses SmartPLS software. The findings of this study indicate that students' financial literacy positively impacts their risky credit behavior. This finding also explains that financial self-efficacy mediates the relationship between financial literacy and credit risk behavior.